2010
DOI: 10.3109/14992027.2010.525754
|View full text |Cite
|
Sign up to set email alerts
|

A multi-component intervention to promote hearing protector use among construction workers

Abstract: Hearing protection devices (HPD) remain a primary method of prevention of noise-induced hearing loss despite their well-known limitations. A three-pronged intervention to increase HPD use was conducted among construction workers and included a baseline hearing loss prevention training, follow-up 'toolbox' (TB) reinforcement trainings, and use of a personal noise level indicator (NLI). A total of 176 subjects on eight sites completed three assessments. Prior to intervention, HPDs were used an average of 34.5% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 30 publications
0
48
1
6
Order By: Relevance
“…Compliance with legislation regarding the performance of audiometry has not always occurred (3) in spite of its importance, because auditory monitoring is fundamental to assess prevention actions (4) . Other studies have also observed an increase in workers' knowledge about preservation of hearing at work after interventions, but with educational strategies and approaches different from that developed in the present study, evidencing percentage changes smaller than those found here (6)(7)(8)11,27,28) . In the USA, a study on educational intervention was conducted with 176 construction workers aiming to increase the use of HPDs.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Compliance with legislation regarding the performance of audiometry has not always occurred (3) in spite of its importance, because auditory monitoring is fundamental to assess prevention actions (4) . Other studies have also observed an increase in workers' knowledge about preservation of hearing at work after interventions, but with educational strategies and approaches different from that developed in the present study, evidencing percentage changes smaller than those found here (6)(7)(8)11,27,28) . In the USA, a study on educational intervention was conducted with 176 construction workers aiming to increase the use of HPDs.…”
Section: Discussioncontrasting
confidence: 58%
“…The strategy used was to convey basic information and additional extensive information in four training sessions for one group, and only basic information in a single training session for another group. The authors observed increased (12.1%) use of HPDs and greater content absorption in the group that received basic educational intervention and reinforcement training in four sessions (7) . In Brazil, a study aiming to verify the effectiveness of an educational training intervention, using individual conversation and illustrative material at the time of audiometry, was conducted with 78 workers divided into a research group (44 workers) and a control group (34 workers).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Because the only study that describes the effect of follow-up training failed to demonstrate any benefit from it,12 there was no benchmark against which to compare the health promotion activity.…”
Section: Introductionmentioning
confidence: 99%